Hemorrhoidal Disease in the Diabetic Population: The Effects of Glucose Regulation and Lipid Profile - Enver Ciftel; Sedat Ciftel; Serpil Ciftel; Filiz Mercantepe; Remzi Adnan Akdogan (Life)
Background: Hemorrhoidal disease is a common anorectal condition characterized by the enlargement and distal displacement of the typical vascular structures in the anal canal. The relationship between DM, lipid metabolism, and hemorrhoidal disease remains underexplored. This study aims to investigate the prevalence of hemorrhoids and the association between glycemic control and lipid profile in diabetic patients. Methods: This retrospective cross-sectional study included 752 patients who underwent colonoscopy at Erzurum Regional Training and Research Hospital between June 2021 and August 2024. The study population comprised 452 patients with type 2 diabetes mellitus (mean age 63.4 ± 11.0) and 300 nondiabetic patients (mean age 62.8 ± 10.8). The presence of hemorrhoids was confirmed through colonoscopy. Glycemic control parameters, lipid profile, and other biochemical parameters were analyzed. Results: Hemorrhoids were found in 47.3% (n = 214) of diabetic patients and 17.3% (n = 52) of nondiabetic patients, indicating a significantly higher prevalence in the diabetic group (OR = 4.3, CI = 3.0–6.2, p < 0.001). Diabetic patients with hemorrhoids had significantly higher mean HbA1C (8.1 ± 2.1 vs. 7.5 ± 1.8, p < 0.001), low-density lipoprotein (p < 0.001), and triglyceride levels (p = 0.005) compared to those without hemorrhoids. Additionally, a longer duration of diabetes and higher hypertension prevalence were observed in the hemorrhoid group. Conclusions: The findings suggest that poor glycemic control and dyslipidemia are significantly associated with an increased prevalence of hemorrhoids in diabetic patients. These results highlight the importance of comprehensive management of diabetes, including lipid control, to potentially reduce the risk of hemorrhoidal disease.